Exploring the Impact of Anti-Fraud Controls on Occupational Fraud - Jain, Gunjan (Digital Repository of Theses - SSBM Geneva, 2025)
This dissertation focuses on adaptation to anti-fraud controls in view of changes in business conditions, namely those brought upon by the virus commonly known as COVID-19. Again, after the pandemic, the efficacy of anti-fraud mechanisms or systems within different departments at an organizational, business, and sectoral level of occupational fraud within an organization comes into question. Of interest to the study at hand is also the identification of areas where changes have been affected and examining the effectiveness they have had while attempting to control cases of occupational fraud. This study embraces a mixed-methods approach through quantitative and qualitative survey to garner responses across different industries. It considers the various specific anti-fraud strategies for different departments, such as HR, Finance, Operations, and IT, besides sectoral and organizational size differences. Some major themes in these measures range from traditional ones involving internal controls and audits to modern techniques of AI, machine learning, and data analytics. The results show that organizations with a full anti-fraud framework tend to report fewer fraud incidents, emphasizing proactive steps like employee training, strong internal controls, and real-time data monitoring. Similarly, the adaptation to enhanced cyber security protocols, remote fraud monitoring tools, and better coordination between departments since the pandemic was partial across different departments and sectors. Large organizations had advanced systems, while SMEs faced resource allocation challenges and difficulties in integrating technology. The study concludes that even though traditional anti-fraud measures are still relevant, integration of innovative technological solutions and frequent training among employees is hugely required in the fight against contemporary fraud risks. Additionally, instilling a culture of ethical accountability and increasing inter-agency collaboration will go a long way toward strengthening organizational resilience against occupational fraud. It is a study adding to existing knowledge through actionable insights in the direction of anti-fraud strategies and thus provides a framework from which organizations can adapt measures to suit their needs and specific vulnerabilities. This dissertation underlines the dynamic character of fraud prevention and accordingly proposes adaptive strategies for mitigating occupational fraud in a world where business is becoming increasingly complex and digitalized.